Early Childhood Caries in 3 to 5 Year Old Children in Trinidad and Tobago - Tricia Percival; Julien Edwards; Salvacion Barclay; Bidyadhar Sa; Md Anwarul Azim Majumder (MDPI AG, 2019)
Background: This study was done to evaluate the prevalence and contributory factors of early childhood caries (ECC) and severe ECC (S-ECC) among preschool children of Kindergartens and Early Childhood Centres in Trinidad and Tobago. Methods: A cross-sectional study was carried out involving 342 preschool children aged 3 to 5 years. The school staff distributed a structured questionnaire to the children to be completed by the mother. Clinical examinations were conducted by calibrated examiners. Statistical significance was set at p < 0.05 in all analyses. Results: The prevalence of ECC and S-ECC was 50.3% and 52.3%, respectively. Dietary and oral hygiene factors particularly with bottle feeding and high plaque levels were major contributors to dental caries in this population. Conclusion: ECC and S-ECC are significant issues that occur in preschool children in Trinidad and Tobago. The development of ECC and S-ECC can be attributed to certain environmental factors like dietary habits and oral hygiene practices. Early dental assessment, broad-based oral health education programmes, increased parental/guardian engagement during oral hygiene practices and greater access to facilities for early childhood caries prevention and management can help alleviate the problems of ECC and S-ECC in this population.